THE ROLE OF AUTHENTIC MATERIALS IN TEACHING ENGLISH (Academia Science Repository, 2023)
This article describes in detail the role and place of authentic materials in foreign language and English teaching today, the main tasks facing foreign language teachers, and the analysis of the opinions expressed by the most famous authors about authentic materials.